Your knife, my heart - Moronova, K. M. (Dark forces, 2026)
"Cameron Mortem has a problem--he can't stop killing his partners. Officially labeled clinically insane, he's also one of the most lethal assets in the Dark Forces, a brutal underground military operation built on obedience, survival, and silence. But an experimental drug has fractured his control, making him a liability whenever someone else is on the field. As punishment, he's thrown back into the Under Trials-a merciless boot camp designed to break the weak and sharpen the ruthless. His one directive? Don't kill the new girl. Emery Maves narrowly escapes a death sentence after her own brutal crimes, only to find herself forced into the same violent world. Assigned to Cameron, she's expected to survive the Trials and her partner's unstable nature. But Emery quickly realizes there's more to Cameron than bloodlust and body counts. Beneath the madness lies a terrifying allure--and a strange, dangerous tenderness. As the Trials push them to their limits, Emery must navigate the brutal demands of the Dark Forces while resisting the pull of a man who could just as easily kill her as protect her. And Cameron must fight the one urge he's never been able to overcome"-- Provided by publisher.